IMPROVING WRITING SKILL THROUGH ESA WITH VIDEO ANIMATION OF THE EIGHTH GRADE STUDENTS - Dewa Ayu Ari Wiryadi Joni; Putu Ayu Paramita Dharmayanti; Luh Ketut Sri Widhiasih; Niluh Putudiah Swandewi (Journal on Studies in English Language Teaching (JOSELT), 2022)
The purpose of this study was to know whether or not the writing skill of the eighth-grade students of secondary school can be improved through the implementation of ESA with video animation. The subject was the eighth-grade students of secondary school that consisted of 33 students, 17 females and 16 males. The researchers used some instruments such as a pre-test, post-tests and a questionnaire to collect the data in this present study. This classroom action research that conducted into two cycles, such as cycle I and cycle II. Each cycle consisted of two sessions. Based on the result of pre-test, the students had problems in writing. Based on the data of mean scores from pre-test until posttests, it showed that the mean score of pre-test was 39.15, post-test I was 68.36 and post-test II was 78.03. It meant that there were significant improvements in the subjects. In addition, the data also was supported by administering a questionnaire. The result of the questionnaire showed more than 90% of subjects gave positive responses through the implementation of ESA to improve their writing skill. In conclusion, writing skill of the eighth grade students of secondary school could be improved through ESA with video animation.